2004
DOI: 10.1023/b:maci.0000025728.54271.27
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Breastfeeding Intention Among Low-Income Women

Abstract: Women at high risk for not wanting to breastfeed can be identified for additional support. Interventions should focus on improving breastfeeding knowledge, enhancing confidence in one's ability to breastfeed, and overcoming barriers to breastfeeding, especially lack of social support, among low-income women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
124
1
5

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 154 publications
(146 citation statements)
references
References 23 publications
12
124
1
5
Order By: Relevance
“…Our results suggest that some, but not all, of the psychosocial factors we assessed were predictive of EBF intention among rural Bangladeshi women, which is similar to previous studies in other settings that consider attitudes (20,21) and knowledge (22) in relation to breast-feeding intentions. Prenatal attitudes and self-efficacy were not predictive of EBF or full breast-feeding at 3 months of age.…”
Section: Discussionsupporting
confidence: 88%
“…Our results suggest that some, but not all, of the psychosocial factors we assessed were predictive of EBF intention among rural Bangladeshi women, which is similar to previous studies in other settings that consider attitudes (20,21) and knowledge (22) in relation to breast-feeding intentions. Prenatal attitudes and self-efficacy were not predictive of EBF or full breast-feeding at 3 months of age.…”
Section: Discussionsupporting
confidence: 88%
“…This is might be due to increase awareness in breastfeeding among young mothers through social networks, media and introduction of benefits of breastfeeding in the academic curriculum. However, few studies reported older maternal age as the predictive factor of breastfeeding intention (Dungy et al, 2008;Forster, McLachlan, & Lumley, 2006;Mitra et al, 2004).The present study showed that higher education was associated with breastfeeding intention among the mothers. This finding is aligned with a study done in the United States (Colaizy, Saftlas, & Morriss, 2012).…”
supporting
confidence: 49%
“…Infants who were not breastfeeding may expose to higher risks of infectious morbidity, as well as associated with increased risks of childhood obesity, leukemia, type I and II diabetes and sudden infant death syndrome (SIDs) (Stuebe, 2009). Breastfeeding intention is a significant predictor of positive breastfeeding outcomes, having an intention to breastfeed linked to early initiation and longer duration of breastfeeding (Donath & Amir, 2003;Mitra, Khoury, Hinton, & Carothers, 2004;Tarrant, Younger, Sheridan-Pereira, White, & Kearney, 2010a). Intention is an immediate precursor of behaviour and is defined as the perception of an individual towards performance of a particular behaviour (Ajzen & Fishbein, 1980).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations